The Negotiating Strategy in Translating the Untranslatable Concepts in Al-Qur'an - Baharuddin, Baharuddin (Master Program in Linguistics, Diponegoro University, 2023)
This article studies the translation of Al-Qur’an into English. Some facts (concepts, notions, perceptions, images, consideration) degrade from those contained in the original language. This may be due to some translation problems related to the theory of translation and semantics, semiotics, pragmatics and so on. Lexical problem in terms of how dictions were selected and decided to translate a certain word in the language of Al-Qur’an. In translation, two translations by two different translators, Dawood and Pickthal, were examined to see how they tried to employ corresponding words in translating terms used by Al-Qur’an. When the meaning may be translated well, the beauty of the verse is degraded very much or even not grasped at all. In this part, two translations from Yusuf Ali and Shakir were compared to see how the beauty of the verse was transferred well. As a conclusion of this study, some facts related to the meaning of words and beauty of verses were untranslated correspondingly. Many other disciplines of language studies should be involved to translate Al-Qur’an